ECONOMIC ASPECTS REGARDING INDIVIDUALS' INVESTMENTS IN PRECIOUS METALS - Marian ȚAICU; Ovidiu Aurel GHIUȚĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
Precious metals were discovered and appreciated for their qualities in ancient times. Initially used as jewelry, with the evolution of humanity, precious metals have become useful in a wide range of fields, and are used nowadays both in the industry and as investment assets. For individual investors, investments in precious metals have certain peculiarities that will be discussed here in below.